Peningkatan Pemahaman Konsep Perpindahan Kalor dengan Metode Eksperimen di Kelas V SDN Rembang 2 Kota Blitar - Wiwit Rahmawati (Civiliza Publishing, 2021)
Abstract. Understanding the concept of science must be carried out with a process of doing it yourself, especially on learning materials related to science chemistry or science physics. In the study of Heat Transfer in Class V SDN Rembang 2, Sananwetan District, Blitar City, in the 2020/2021 academic year, it can be seen that there are still many students who do not understand the concept, so the results obtained in completeness are less than 35% of the total number of students. This is because students in this learning year do online learning, and teachers do monotonous learning so that it does not attract students. Based on the results that are still lacking, a research is conducted on learning science content in class V. The research used is a qualitative research on science learning with the type of Class Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The method used to solve problems in learning Heat transfer is the experimental method, which is a way of teaching and learning that involves students by experiencing and proving themselves the process and results of the experiment which are closely related to everyday life.